A diradical based on odd-electron σ-bonds - Wenbang Yang (Nature Portfolio, 2020)
Stable diradicals are generally based on two s/p-localized or π-delocalized unpaired electrons (radicals). Here, the authors report a dication diradical that is based on two Se∴Se three-electron σ-bonds.